El grito de los «fracasados». Sobre Mariluz y el largo etcétera de Alejandro Cuevas - Gutkowska-Ociepa, Katarzyna (Studia Romanica Posnaniensia, 2020)
The purpose of the article is to reflect upon the role of political context in the short story collection published by Alejandro Cuevas in 2018: Mariluz y el largo etcétera. The politics is defined here according to one of the most commented theory of the aesthetics by Jacques Rancière and his concept of the “sensible”. It also focuses on the impact of the democratization of the subject-matter presented in the literary works of art since 19th century. Rancière’s approach together with considerations by Gonzalo Navajas, Vicente Luis Mora and others on the specificity of Spanish contemporary narrative reveal the intensity of the collective anxiety and problematical aspects of socio-economic reality that permeate the short stories by Cuevas, letting the reader notice in them glimpses of the series of issues regarding the Bubble Generation, sometimes also referred to as the Millennials or the 15-M Movement and other groups forming Spanish contemporary society. Cuevas manages to build in the political context without afflicting neither the humour nor the engaging expressiveness of his literary style.